Population-based detection of lynch syndrome in young colorectal cancer patients using microsatellite instability as the initial test - Sehofield, L.; Watson, N.; Grieu, F.; Wei, Q.; Zeps, Nikolajs; Harvey, J.; Stewart, C.; Abclo, M.; Goldblatt, J.; Iacopetta, B. (John Wiley & Sons, Inc., 2009)
Approximately 1-2% of colorectal cancers (CRC) arise because of germline mutations in UNA mismatch repair genes, referred to as Lynch syndrome. These tumours show microsatellite instability (MSI) and loss of expression of mismatch repair proteins. Pre-symptomatic identiication of mutation carriers has been demonstrated to improve survival; however, there is concern that many are not being identified using current practices. We evaluated population-based MSI screening of CRC in young patients as a means of ascertaining mutation carriers. CRC diagnosed in patients aged <6% years were identiied from pathology records. No prior information was available on family history of cancer. PCR techniques were used to determine MSI in the BAT-26 mononucleotide repeat and mutation in the BRAF oncogene. Loss of MI.H1. MSH2, MSH6 and PMS2 protein expression was evaluated in MSI+ tumours by immunohistochemistry. MSI+ tumours were found in 105/1,344 (7.8%) patients, of which 7 were excluded as possible Lynch syndrome because of BRAF mutation. Of the 98 "red lag" cases that were followed up, 25 were already known as mutation carriers or members of mutation carrier families. Germline test results were obtained for 35 patients and revealed that 22 showed no apparent mutation, 11 showed likely pathogenic mutations and 2 had unclassified variants. The proportion of MSI+ cases in different age groups that were estimated to be mutation carriers was 89% (<30 years), 83% (30-39), 68% (40-49) and 17% (50-59). We recommend MSI as the initial test for population-based screening of Lynch syndrome in younger CRC patients, regardless of family history. ©2008 Wiley-Liss, Inc.